Environmental Marine Degradation of Pla/Wood Composite as an Alternative Sustainable Boat Building Material - Çamll,S.B.; Neşer,G.; Sözen,A. (Sciendo, 2024)
IIn this study, which can be considered a contribution to the global effort to produce sustainable materials and to search new manufacturing methods for the boat building industry, the performance of a 3D printable polylactic acid and recycled wood (PLAW) composite was investigated under the simulated operational conditions of a boat. The wood used in the composite was yellow pine (Pinus sylvestris), a local wood widely used in boat building and 8% by weight in the composite. For the study, tensile and compressive strength tests were performed in both atmospheric and post-aging conditions, using composite samples produced by the additive manufacturing method. The durations of the accelerated aging before the experiments were one, two and four weeks. During these aging periods, water spraying, a salty fog environment and a drying cycle were applied at elevated temperatures and at equal time intervals, daily. The effect of wood additive on the composite and the joining efficiency of the components were also examined with scanning and optical microscopes. The performance of the obtained composite and the effects of aging on performance were measured using two different thermal analyses: differential scanning calorimetry and thermogravimetric analysis. From the results obtained, it can be seen that PLAW composite can be used in the manufacture of structural elements subjected to relatively low loads in boats. It is an option that will provide integrity in the future interior design of wooden boats. © 2024 Selin Barlş Çamll et al., published by Sciendo.
Keywords: Additive manufacturing; Environmental marine degradation; Fused filament fabrication (FFF); PLA and recycled wood (PLAW) composite; Wooden boat building; Yellow pine (Pinus sylvestris)